Dr lecturer: Effects of Environmental antecedents on Financing BOT Projects in Africa, A Case of the Rift Valley Consortium Kenya - okelo, stephen (Archives of Business Research, 2021)
The purpose of this study was to investigate the effects of Environmental factors on financing BOT( Build Operate Transfer) infrastructure projects, Infrastructure plays a crucial role in the drive for achieving development by providing energy, transportation, and water. There have been ups and downs in the degree of emphasis placed on infrastructure, but infrastructure has remained the largest component of the public investment programs in developing countries 62 % of gross domestic product (GDP). Nearly half of the international financial institutions’ project lending to developing countries goes to infrastructure. The study used a mixed method research design; with a target population of 720 employees of rift valley rail consortium and government of Kenya representatives of which a sample of 338. The study used questionnaires and interview guides to collect data. Data were collected by administering questionnaires to the respondents while senior managers and government officials were interviewed. Data collected was coded. Qualitative data was analyzed using themes and sub-themes, while quantitative data was analyzed by the use of inferential statistics, of which the frequency percentages were calculated, data were cross-tabulated to establish the relationship within the variables and finally, a Wald test statistic was conducted to measure the strength and direction of relationship within the variables. A calculated Pearson Chi-Square of 0.818 lead to rejection of the null hypothesis and therefore, there is a significant relationship between Environmental antecedents and financing of BOT projects. The study recommended that there is a need for policies to be articulated on tackling the rise of environmental destruction due to the BOT projects in Kenya.